Accuracy verification and correction of ascending and descending SBAS- and MSBAS-InSAR in monitoring mining surface subsidence. Issue 27 (13th December 2022) - Han, Yu; Tao, Qiuxiang; Liu, Guolin; Hou, Anye; Guo, Zaijie; Wang, Fengyun
Abstract: To address the position offset and insufficient monitoring accuracy of surface subsidence in mining areas using the SBAS-InSAR, this study uses the MSBAS-InSAR method. However, the quality of correction results is poor owing to the ill-posed observation equation of MSBAS. Therefore, the SBAS-based decomposition method is used, which directly decomposes the ascending and descending SBAS monitored LOS results to circumvent the ill-posed problem of the MSBAS and obtain higher-accuracy 2D deformation results. A real mining area was taken as the research site and monitored using the SBAS, MSBAS, and the SBAS-based decomposition method. The accuracy and effectiveness of the surface deformation results obtained by these methods were compared and verified with the levelling data in the same period. The results show that the SBAS-based decomposition method can significantly reduce the position offset and improve the monitoring accuracy of single-track SBAS, and circumvents the ill-posed problem of MSBAS.